Internet-of-things smart-packs for medication adherence - Ching, Ming Yang (Nanyang Technological University, 2023)
This project pertains to an Internet-of-Things (IoT) system for medication adherence. The objective of this project is to monitor the adherence of patients in taking medication prescribed by their healthcare provider. Globally, non-adherence to medication regimens raises patient's risk of severe health complications, hospital readmissions, and mortality. Non-adherence to medication costs the world an estimated US$700B annually. With recent drug shortages due to the pandemic and other causes, medication adherence is now more critical than ever. The IoT system used in this project is designed for real-time monitoring of patient’s adherence in taking an anti-coagulant drug by a local hospital for a clinical trial. It comprises Smart Blister Packs, smartphone apps, and a cloud (server) system. The Smart Blister Packs contains a drug blister pack and a microcontroller that transmits information to the application and the cloud. Our team developed a low-cost, non-intrusive, convenient, and reliable IoT system compared to existing technologies. Nonetheless, there remains areas of improvement, such as the lack of iOS applications limiting a large proportion of patients. To improve ease of use, the Smart Blister Packs should be simple to program and compatible with both the existing Android app and the soon to be developed iOS app. This project addresses the problems and develops the iOS app for the patients to use. This project's three main contributions are a working iOS application to interface with the blister pack, a Python script to simplify firmware programming for hospital users, and a cross-compatible firmware for both iOS and Android applications.